Understanding the Entanglement: Neutrophil Extracellular Traps (NETs) in Cystic Fibrosis - Martínez-Alemán, Saira R.; Campos-García, Lizbeth; Palma-Nicolas, José P.; Hernández-Bello, Romel; González, Gloria M.; Sánchez-González, Alejandro (Frontiers in Cellular and Infection Microbiology, 2017)
Cystic fibrosis is an autosomal recessive disorder caused by mutations in the gene that codes for the cystic fibrosis trans-membrane conductance regulator. These mutations result in abnormal secretions viscous airways of the lungs, favoring pulmonary infection and inflammation in the middle of neutrophil recruitment. Recently it was described that neutrophils can contribute with disease pathology by extruding large amounts of nuclear material through a mechanism of cell death known as Neutrophil Extracellular Traps into the airways of patients with cystic fibrosis. Additionally, NETs production can contribute to airway colonization with bacteria, since they are the microorganisms most frequently found in these patients. In this review, we will discuss the implication of individual or mixed bacterial infections that most often colonize the lung of patients with cystic fibrosis, and the NETs role on the disease.